Equity research: GlaxoSmithKline strategy and forecast - Wei, Zirui (2021)
As we are living in a Covid-19 spreading environment, people can never feel more important and vulnerable the health itself is. Naturally, we feel interested to do an equity research on a healthcare company. Coincidently, the news that an HPV nine-valent vaccine was finally available in mainland China and the exporter ——GSK arose our interest. Thus, we did a brief investigation into it and found this company is appropriate to be our research target. Our work industry and company overview, macroeconomics environment, past analysis, forecast and valuation. It is based on the corporate valuation, financial statement analysis and financial report knowledge that we learned at Novasbe. We started from analyzing the company and its macro environment, we did a forecast on its revenue, income statement, balance sheet and cash flow statement. Note that instead of choosing GDP and population as drivers, we decided to not apply any drives because it’s more reasonable to forecast its revenue based on its products and patent. Then, A APV model has been applied to deal with the valuation. We got a brief conclusion that GSK’s stock is undervalued and it’s worth to buy GSK stocks with an expected return of 23.0%After completing this study, we could know better not only our target company GSK but also other pharma companies. Our equity research can serve as a good guideline for investors who want to know about healthcare stocks.